2017
DOI: 10.1111/1462-2920.13929
|View full text |Cite
|
Sign up to set email alerts
|

Genomes of rumen bacteria encode atypical pathways for fermenting hexoses to short‐chain fatty acids

Abstract: Bacteria have been thought to follow only a few well-recognized biochemical pathways when fermenting glucose or other hexoses. These pathways have been chiseled in the stone of textbooks for decades, with most sources rendering them as they appear in the classic 1986 text by Gottschalk. Still, it is unclear how broadly these pathways apply, given that they were established and delineated biochemically with only a few model organisms. Here, we show that well-recognized pathways often cannot explain fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…While it would be possible to miss this gene from an individual single-cell genome, it is highly unlikely that we would specifically miss enolases from ∼10 genomes, which constitute the metagenome. So far, only 6 rumen bacterial genomes have been described that are lacking enolase; 5 from Firmicutes and 1 from Prevotella (38,39). An alternative, the methylglyoxal shunt, has been suggested to bypass enolase, where dihydroxyacetone phosphate is converted to pyruvate or L-lactate via methylglyoxal (38).…”
Section: Discussionmentioning
confidence: 99%
“…While it would be possible to miss this gene from an individual single-cell genome, it is highly unlikely that we would specifically miss enolases from ∼10 genomes, which constitute the metagenome. So far, only 6 rumen bacterial genomes have been described that are lacking enolase; 5 from Firmicutes and 1 from Prevotella (38,39). An alternative, the methylglyoxal shunt, has been suggested to bypass enolase, where dihydroxyacetone phosphate is converted to pyruvate or L-lactate via methylglyoxal (38).…”
Section: Discussionmentioning
confidence: 99%
“…In the reduction of crotonyl-CoA to butyryl-CoA, Fd ox is simultaneously reduced by a second molecule of NADH to Fd red 2− in a process called electron bifurcation (Buckel and Thauer, 2013; Figure 3A; see also section "The Role of Dihydrogen as an Intercellular Electron Carrier"). The oxidation of Fd red 2− so formed by electron bifurcation can result in H + extrusion and ATP generation by ETLP (Hackmann and Firkins, 2015;Hackmann et al, 2017).…”
Section: Carbohydrate Metabolism and Production Of Volatile Fatty Acidsmentioning
confidence: 99%
“…A recent study of the metabolic pathways present in the genomes of a number of rumen bacteria identified several non-standard metabolic pathways that are not adequately represented in current databases (Hackmann et al, 2017). Hackmann and colleagues found that the recognized pathways for metabolizing pentose and hexose sugars to short-chain fatty acids do not adequately explain the fermentation products generated by a wide range of rumen bacteria (Hackmann et al, 2017). They found that 44% of these bacteria encoded atypical metabolic pathways and identified several that are completely novel.…”
Section: Composition Of the Rumen Microbiomementioning
confidence: 99%